An evidence-based, point-of-care tool to guide completion of asthma action plans in practice. Issue 5 (2nd May 2017) - Kouri, Andrew; Boulet, Louis-Philippe; Kaplan, Alan; Gupta, Samir
Asthma action plans (AAPs) reduce healthcare utilisation, improve quality of life and are recommended across guidelines. However, fewer than 25% of patients receive an AAP, partly due to prescribers' inability to complete "yellow zone" instructions (how to intensify therapy for acute loss of control). We sought to review best evidence to develop a practical, evidence-based tool to facilitate yellow zone guidance in adults. We reviewed recent asthma guidelines and adult studies addressing acute loss of asthma control (January 2010 to March 2016). We developed evidence-based rules for yellow zone therapy and operational guidelines to maximise adherence and minimise errors. We reviewed three guidelines and 11 manuscripts (2486 abstracts screened). Recommendations were comparable but some areas lacked guidance. For 15/43 asthma regimens, the commonly recommended four- to five-fold yellow zone inhaled corticosteroid dose increase was problematic due to regulatory dose limits. We identified evidence-based alternatives for 8/15 regimens. Operational guidance included increasing to a maximum of four inhalations while maintaining baseline inhaler frequency and device in the yellow zone. We developed a practical implementation tool to facilitate AAP delivery at the point of care, addressing existing gaps and uncertainties. Our tool should be implemented as part of a multifaceted approach to augment AAP usage. New tool brings complex evidence to the point-of-care, guiding providers on how to create the best #asthmaactionplan http://ow.ly/rmFu30a9neW